The Impact of CSR Practices on Employer Attractiveness : Perspectives of Young Professionals in International Companies - Korhonen, Emma (My University, 2026)
This master’s thesis examines how young business professionals perceive corporate social responsibility (CSR) and how these perceptions influence employer image and employer attractiveness. The starting point of the study is the observation that CSR has become a central element of organizational communication and employer branding, yet its credibility and significance in employer evaluation vary. The objective of the thesis is to deepen understanding of how young professionals interpret CSR and the criteria they use to assess its credibility in an employer context. The theoretical framework of the study is based on Institutional Theory, Stakeholder Theory, and Signaling Theory. Through these perspectives, CSR is examined as part of the evaluation of employer legitimacy, credibility, and attractiveness. Key concepts include corporate social responsibility, authenticity, employer image, employer attractiveness, and credibility. The study adopts a qualitative research approach. The empirical data consist of eight semi-structured interviews conducted with Master’s-level business students who simultaneously have work experience in international companies. The data were analyzed using thematic analysis. The findings indicate that the authenticity of CSR functions as a central criterion of credibility in employer evaluations. CSR is not assessed based on its mere presence or visibility, but on how consistently, transparently, and verifiably responsibility is implemented as part of business operations. Symbolic or communication-driven CSR initiatives tend to generate distrust, whereas long-term practices, reporting, and external verification strengthen employer credibility. The influence of CSR on employer attractiveness appears conditional. CSR may function as an exclusionary factor that weakens employer image, as a differentiating factor between otherwise similar employers, or as a source of pride and identification within employment relationships. The weight of CSR varies according to individual values and the economic context; however, weak or non-credible CSR consistently undermines employer image. In addition, the findings show that young professionals do not form a homogeneous group in terms of CSR expectations. CSR priorities vary, for example, between equality, environmental responsibility, and employee well-being, and these differences reflect education, family background, and the institutional environment. Overall, the results demonstrate that genuinely verifiable and balanced CSR constitutes a central element of employer credibility and legitimacy in the evaluations of young business professionals.

Tämä pro gradu-tutkielma tarkastelee, miten nuoret liikealan ammattilaiset hahmottavat yritysvastuun (CSR) merkityksen ja miten nämä käsitykset vaikuttavat työnantajakuvaan ja työnantajan vetovoimaan. Tutkimuksen lähtökohtana on havainto siitä, että yritysvastuusta on tullut keskeinen osa organisaatioiden viestintää ja työnantajamielikuvan rakentamista, mutta sen uskottavuus ja merkitys työnantajan arvioinnissa vaihtelevat. Tutkielman tavoitteena on syventää ymmärrystä siitä, millä tavoin nuoret ammattilaiset tulkitsevat yritysvastuuta ja millaisin kriteerein he arvioivat sen uskottavuutta työnantajakontekstissa. Tutkimuksen teoreettinen viitekehys rakentuu institutionaalisen teorian, sidosryhmäteorian ja signaaliteorian varaan. Näiden avulla yritysvastuuta tarkastellaan osana työnantajien legitimiteetin, uskottavuuden ja vetovoiman arviointia. Keskeisiä käsitteitä ovat yritysvastuu, aitous, työnantajakuva, työnantajan vetovoima sekä uskottavuus. Tutkimus on laadullinen, ja aineisto koostuu kahdeksasta puolistrukturoidusta haastattelusta, jotka on toteutettu liikealan maisterivaiheen opiskelijoille, joilla on samanaikaisesti työkokemusta kansainvälisissä yrityksissä. Aineisto on analysoitu temaattisen analyysin avulla. Tulokset osoittavat, että yritysvastuun aitous toimii keskeisenä uskottavuuden kriteerinä työnantajien arvioinnissa. Yritysvastuuta ei arvioida sen olemassaolon tai näkyvyyden perusteella, vaan sen mukaan, miten johdonmukaisesti, läpinäkyvästi ja todennettavasti vastuullisuutta toteutetaan osana liiketoimintaa. Symboliset tai viestintävetoiset yritysvastuutoimet herättävät epäluottamusta, kun taas pitkäjänteinen toiminta, raportointi ja ulkoinen varmennus vahvistavat työnantajan uskottavuutta. Yritysvastuun vaikutus työnantajan vetovoimaan näyttäytyy ehdollisena. Se voi toimia poissulkevana tekijänä, joka heikentää työnantajakuvaa, erottelevana tekijänä muuten samankaltaisten työnantajien välillä tai ylpeyden ja samaistumisen lähteenä työsuhteessa. Yritysvastuun painoarvo vaihtelee yksilöllisten arvojen ja taloudellisen tilanteen mukaan, mutta heikko tai epäuskottava yritysvastuu heikentää johdonmukaisesti työnantajamielikuvaa. Lisäksi havaitaan, että nuoret ammattilaiset eivät muodosta yhtenäistä ryhmää yritysvastuuseen liittyvien odotusten suhteen. Yritysvastuun painotukset vaihtelevat esimerkiksi tasa-arvon, ympäristövastuun ja työntekijöiden hyvinvoinnin välillä, ja nämä erot heijastavat koulutusta, perhetaustaa ja institutionaalista ympäristöä. Tutkielman tulokset osoittavat, että aidosti todennettava ja tasapainoinen yritysvastuu on keskeinen osa työnantajan uskottavuutta ja legitimiteettiä nuorten liikealan ammattilaisten arvioissa.
Keywords: fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business